2016
DOI: 10.1021/acs.chemrev.6b00098
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Imprinted Membranes: Past, Present, and Future

Abstract: More than 80 years ago, artificial materials with molecular recognition sites emerged. The application of molecular imprinting to membrane separation has been studied since 1962. Especially after 1990, such research has been intensively conducted by membranologists and molecular imprinters to understand the advantages of each technique with the aim of constructing an ideal membrane, which is still an active area of research. The present review aims to be a substantial, comprehensive, authoritative, critical, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
112
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(121 citation statements)
references
References 255 publications
0
112
0
1
Order By: Relevance
“…Among the different types of enantioselective membranes, only some MIMs have been developed after the last review (2016) specifically focusing this type of membranes [52].…”
Section: Imprinted Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the different types of enantioselective membranes, only some MIMs have been developed after the last review (2016) specifically focusing this type of membranes [52].…”
Section: Imprinted Membranesmentioning
confidence: 99%
“…In fact, it was found that molecularly imprinted polymers (MIPs) exhibit well-defined structures, high selectivity and binding affinity for the target molecules, considering that the caves created within MIPs are complementary to them in shape, size, configuration and functional moieties. Moreover, they have excellent chemical properties and comparing with other methods to introduce chiral recognition sites in polymeric membranes, the preparation of molecularly imprinted membranes (MIMs) are simple, low-cost, and effective [45,52]. Various review articles are found in literature regarding MIPs [45,48,49,[100][101][102][103][104][105][106][107] and among them focusing on MIMs [52,98,99].…”
Section: Introductionmentioning
confidence: 99%
“…proposed the use of molecular imprinting of supramolecular hydrogels for drug delivery of small molecules in 2007, there has been virtually no progress in that direction since then. Nevertheless, the field of molecular imprinting has continued to grow, but growth has primarily been in two areas: molecular detection/sensing and separation . The separations field faces the same challenge as the drug delivery field did, in generating high affinities toward small molecules using only linear polymeric systems of low‐affinity components, so investigations have continued using novel matrix components including binary and ternary deep eutectic solvents, ionic liquids, and zwitterionic polymers .…”
Section: Introductionmentioning
confidence: 99%
“…Since the advantages of solid membranes are high-throughput, energy-saving, pollution-free, low-cost, and easy operation, solid membrane technologies have been widely used in the desalination of seawater, wastewater treatment, chemical engineering, the medical field, metallurgy, etc. [8][9][10][11][12][13][14][15] Recently, some new optical resolution membranes have also been reported. [8][9][10][11][12][13][14][15] Recently, some new optical resolution membranes have also been reported.…”
Section: Introductionmentioning
confidence: 99%